Zarządzanie strategiczne w polskich gminach w świetle wyników badań ankietowych - Ziółkowski, Marek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
As results of questionnaire research show the situation in usage of basic strategic management tools in Polish communities differs from desirable condition. These tools are not used commonly, which means that many territorial governments are still looking on commune management problems through prism of current or tenure actions. This is administration management model. Idea of a new approach has to depend on fully understanding of local development processes and their exterior conditions (especially progressive globalization of society, economic, ecologic processes and region and commune competitiveness as a crucial success indicator in development politics) and on effective steering these processes in a longer time horizon (a horizon of over ten years). These demands are met by strategic management which is the most creative element New Public Management, what brings advantages for communities. Experiments in this area show that consistent usage of strategic management tools contributes to achieving better effects of management. Favorable factor and "extracting this kind of action" factor is European Union, in specific its financial help for communes from structural funds and Cohesion Fund for realization of municipal investments. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 633-639